The marginal cells of the Caenorhabditis elegans pharynx scavenge cholesterol and other hydrophobic small molecules - Muntasir Kamal (Nature Portfolio, 2019)
The C. elegans nematode worm is a filter-feeder and requires dietary sources of cholesterol. Here, the authors show that the C. elegans pharynx works as a filter to scavenge hydrophobic small molecules from its surrounding liquid environment.